2015
DOI: 10.18805/ijar.6695
|View full text |Cite
|
Sign up to set email alerts
|

Effect of deworming regimen on helminths and growth performances in growing Ganjam goats

Abstract: Present work was carried out in the Ganjam Field Unit of AICRP on Goat improvement, Odisha to study the effect of deworming regimen on helminths and growth performances in growing Ganjam goats. It was found that deworming by using Ivermectin and Fenbendazole or Oxyclozanide and Levamisole preparation has got a significant effect on Ganjam kids with respect to body weight gain, haemoglobin, serum total protein, albumin and parasitic load. The effect of Ivermectin and Fenbendazole combination was found to be sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The helminth infestation in animals may vary from subclinical to severe, which can lead to death depending on the type and number of parasites and animal factors, including age, breed and health status (Schutz et al, 2012). The clinical signs of parasitic infestations are associated with a reduction in productive performance due to anorexia, emaciation, poor growth and anemia (Das et al, 2018;Mohanta et al, 2016). Recent studies showed that infestation with gastrointestinal nematodes could impair the host's immune mechanisms (Hendawy, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The helminth infestation in animals may vary from subclinical to severe, which can lead to death depending on the type and number of parasites and animal factors, including age, breed and health status (Schutz et al, 2012). The clinical signs of parasitic infestations are associated with a reduction in productive performance due to anorexia, emaciation, poor growth and anemia (Das et al, 2018;Mohanta et al, 2016). Recent studies showed that infestation with gastrointestinal nematodes could impair the host's immune mechanisms (Hendawy, 2018).…”
Section: Introductionmentioning
confidence: 99%